2016
DOI: 10.1186/s40064-016-3197-y
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α gene polymorphisms and expression

Abstract: Tumor necrosis factor alpha (TNF-α) is a proinflammatory cytokine with an important role in the pathogenesis of several diseases. Its encoding gene is located in the short arm of chromosome 6 in the major histocompatibility complex class III region. Most of the TNF-α gene polymorphisms are located in its promoter region and they are thought to affect the susceptibility and/or severity of different human diseases. This review summarizes the data related to the association between TNF-α gene and its receptor pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
72
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(86 citation statements)
references
References 78 publications
2
72
1
2
Order By: Relevance
“…TNF-a coding gene (TNF) is found on chromosome 6p21.3 within the MHC region which is characterized by extremely high levels of polymorphism. TNF comprises a large number of polymorphisms, such as À238 A/G, À308 A/G, À857 C/T, and À863 A/C TNF-a promoter polymorphisms [19]. It was reported that the TNF-a-308 polymorphism is related to tuberculosis, some autoimmune disorders, and hepatocellular and breast cancers [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…TNF-a coding gene (TNF) is found on chromosome 6p21.3 within the MHC region which is characterized by extremely high levels of polymorphism. TNF comprises a large number of polymorphisms, such as À238 A/G, À308 A/G, À857 C/T, and À863 A/C TNF-a promoter polymorphisms [19]. It was reported that the TNF-a-308 polymorphism is related to tuberculosis, some autoimmune disorders, and hepatocellular and breast cancers [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies were showed that having an A allele at this position is associated with elevated levels of TNF-α 33 , but other studies were showed that there is no relationship between the two 34 . In addition, studies have shown that A allele is associated with lower TNF-α levels 17,35 . The expression of TNF-α, just like other cytokines is tightly regulated both at the transcriptional and post-transcriptional level.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of TNF-α, just like other cytokines is tightly regulated both at the transcriptional and post-transcriptional level. The polymorphisms located within the regulatory regions of TNF-α have been reported to influence the expression and secretion of this cytokine 35 . In TNF-α -238 and -308 SNP, the presence of the A-allele increases the binding of transcription factor to the promoter region of TNF-α, thereby altering its expression 36 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is currently a lack of data in developmentally appropriate in vitro or in vivo lung models that suggest the polymorphisms impact on the levels of the specific cytokines, a number of other evidences (in non-lung models or non-in vitro/in vivo studies) strongly indicate this possibility. [18][19][20][21][22][23][24][25][26] In this study, we hypothesized that these polymorphisms, which may affect gene expression, could be associated with the risk of BPD among Han Chinese newborns, and we aimed to fill the gap in the literature by investigating the association of these 14 polymorphisms with BPD risk among Han Chinese.…”
mentioning
confidence: 99%